Biosynthesis of silver nanoparticles using Sida acuta extract for antimicrobial actions and corrosion inhibition potential. Issue 8 (3rd April 2019) - Idrees, Muhammad; Batool, Saima; Kalsoom, Tanzila; Raina, Sadaf; Sharif, Hafiz Muhammad Adeel; Yasmeen, Summera
ABSTRACT: Nanotechnology exhibits a multidisciplinary area and gained interests for researchers. Nanoparticles produced via physical and chemical methods affects ecosystem drastically. Green synthesis is the charming technique that is inexpensive and safe for the environment. This study aimed to explore the antibacterial actions of as-synthesized silver nanoparticles (Ag-NPs) against Escherichia coli, Staphylococcus aureus and Streptococcus faecalis . Also, the anti-corrosion actions confirmed that the Ag-NPs proved as good inhibitors. In this way, Ag-NPs were prepared via biosynthesis technique by consuming the ground leaves and stem of ' Sida acuta ' as a capping agent. The Ag-NPs were formed by irradiation of the aqueous solution of silver nitrate (AgNO3 ) with extract of S. acuta stem and leaves. The as-synthesized reaction mixture of Ag-NPs was found to exhibit an absorbance band at 446–447 nm, by an UV/VIS spectrophotometer, which is a characteristic of Ag-NPs due to the surface plasmon resonance absorption band. The X-ray diffraction and transmission electron microscopy (TEM) were used for the confirmation of Ag-NPs' variety dimension, morphology and dispersion. The infrared spectra confirmed the bio-fabrication of the Ag-NPs displayed the existence of conceivable functional groups responsible for the bio-reduction and capping. The antimicrobial actions were measured and the zone of inhibition was compared with standard antibiotics.